Cubic function and Alternating Series 2

Calculus Level pending

Let ( 0 x < 1 ) (0 \leq x <1) .

Let f ( x ) = x 3 + a x 2 + b x + c f(x) = x^3 + ax^2 + bx + c and g ( x ) = n = 1 ( 1 ) n + 1 n 3 x n g(x) = \sum_{n = 1}^{\infty} (-1)^{n + 1} n^3 x^n , where f ( 0 ) = g ( 0 ) , f ( 1 2 ) = g ( 1 2 ) f(0) = g(0), f(\dfrac{1}{2}) = g(\dfrac{1}{2}) and 0 1 2 f ( x ) d x = 0 1 2 g ( x ) d x \displaystyle \int_{0}^{\dfrac{1}{2}} f(x) dx = \int_{0}^{\dfrac{1}{2}} g(x) dx .

Find the area of the region bounded by f f and g g on [ 0 , 1 10 ] [0,\dfrac{1}{10}] to eight decimal places.


The answer is 0.00152029.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
May 14, 2018

Let ( 0 x < 1 ) (0 \leq x <1) .

n = 1 n x n = j = 1 n = j x n = 1 1 x j = 1 x j = 1 1 x ( x ) 1 1 x = x ( 1 x ) 2 \sum_{n = 1}^{\infty} n x^n = \sum_{j = 1}^{\infty} \sum_{n = j}^{\infty} x^n = \dfrac{1}{1 - x}\sum_{j = 1}^{\infty} x^{j} = \dfrac{1}{1 - x}(x)\dfrac{1}{1 - x} = \dfrac{x}{(1 - x)^2}

( x x 1 ) ( 1 x ) ( x x 1 ) = x ( x 1 ) 2 . (\dfrac{x}{x - 1})(\dfrac{1}{x})(\dfrac{x}{x - 1}) = \dfrac{x}{(x - 1)^2}.

n = 1 n 2 x n = j = 1 ( n = j n x n ) = \sum_{n = 1}^{\infty} n^2 x^n = \sum_{j = 1}^{\infty} (\sum_{n = j}^{\infty} n x^n) = 1 1 x j = 1 ( j x j ) + x ( 1 x ) 2 j = 1 x j = \dfrac{1}{1 - x}\sum_{j = 1}^{\infty} (j x^j) + \dfrac{x}{(1 - x)^2}\sum_{j = 1}^{\infty} x^j =

( 1 1 x ) ( x ( 1 x ) 2 ) + ( x ( 1 x ) 2 ) ( x 1 x ) = (\dfrac{1}{1 - x})(\dfrac{x}{(1 - x)^2}) + (\dfrac{x}{(1 - x)^2})(\dfrac{x}{1 - x}) = x 2 + x ( 1 x ) 3 \dfrac{x^2 + x}{(1 - x)^3} .

n = 1 n 3 x n = j = 1 n = j n 2 x n = \sum_{n = 1}^{\infty} n^3 x^n = \sum_{j = 1}^{\infty} \sum_{n = j}^{\infty} n^2 x^{n} = 1 1 x j = 1 j 2 x j + 2 x ( 1 x ) 2 j = 1 j x j + x 2 + x ( 1 x ) 3 j = 1 x j = ( 1 1 x ) ( x 2 + x ( 1 x ) 3 ) + \dfrac{1}{1 - x}\sum_{j = 1}^{\infty} j^2 x^j + \dfrac{2x}{(1 - x)^2}\sum_{j = 1}^{\infty} j x^j + \dfrac{x^2 + x}{(1 - x)^3}\sum_{j = 1}^{\infty} x^j = (\dfrac{1}{1 - x})(\dfrac{x^2 + x}{(1 - x)^3}) + ( 2 x ( 1 x ) 2 ) ( x ( 1 x ) 2 ) + ( x 2 + x ( 1 x ) 3 ) ( x 1 x ) = (\dfrac{2x}{(1 - x)^2})(\dfrac{x}{(1 - x)^2}) + (\dfrac{x^2 + x}{(1 - x)^3})(\dfrac{x}{1 - x}) = x 3 + 4 x 2 + x ( 1 x ) 4 \dfrac{x^3 + 4x^2 + x}{(1 - x)^4}

g ( x ) = n = 1 ( 1 ) n + 1 n 3 x n = n = 1 n 3 ( x ) n = ( x 3 + 4 x 2 x ( 1 + x ) 4 ) = x 3 4 x 2 + x ( 1 + x ) 4 \implies g(x) = \sum_{n = 1}^{\infty} (-1)^{n + 1} n^3 x^n = -\sum_{n = 1}^{\infty} n^3 (-x)^n = -(\dfrac{-x^3 + 4x^2 - x}{(1 + x)^4}) = \dfrac{x^3 - 4x^2 + x}{(1 + x)^4}

Let f ( x ) = x 3 + a x 2 + b x + c f(x) = x^3 + ax^2 + bx + c .

f ( x ) = g ( x ) = 0 c = 0 f(x) = g(x) = 0 \implies c = 0 and f ( 1 2 ) = g ( 1 2 ) = 2 27 f(\dfrac{1}{2}) = g(\dfrac{1}{2}) = \dfrac{-2}{27} \implies 54 a + 108 b = 43 \boxed{54a + 108b = -43} .

Let u = 1 + x d u = d x 0 1 2 g ( x ) d x = 1 3 2 u 3 7 u 2 + 12 u 6 u 4 d u = 1 3 2 1 u 7 u 2 + 12 u 3 6 u 4 d u = u = 1+ x \implies du = dx \implies \int_{0}^{\frac{1}{2}} g(x) dx = \int_{1}^{\frac{3}{2}} \dfrac{u^3 - 7u^2 + 12u - 6}{u^4} du = \int_{1}^{\frac{3}{2}} \dfrac{1}{u} - 7u^{-2} + 12u^{-3} - 6u^{-4} du =

( ln ( u ) + 7 u 6 u 2 + 2 u 3 ) 1 3 2 = (\ln(u) + \dfrac{7}{u} - \dfrac{6}{u^2} + \dfrac{2}{u^3})|_{1}^{\frac{3}{2}} = ln ( 3 2 ) + 14 3 24 9 + 16 27 3 = ln ( 3 2 ) 11 27 \ln(\dfrac{3}{2}) + \dfrac{14}{3} - \dfrac{24}{9} + \dfrac{16}{27} - 3 = \ln(\dfrac{3}{2}) - \dfrac{11}{27}

ln ( 3 2 ) 11 27 = 0 1 2 f ( x ) d x = ( x 4 4 + a x 3 3 + b x 2 2 ) 0 1 2 = 24 + 64 a + 192 b 1536 \implies \ln(\dfrac{3}{2}) - \dfrac{11}{27} = \int_{0}^{\frac{1}{2}} f(x) dx = (\dfrac{x^4}{4} + \dfrac{ax^3}{3} + \dfrac{bx^2}{2})|_{0}^{\frac{1}{2}} = \dfrac{24 + 64a + 192b}{1536} \implies

1728 a + 5184 b = 41472 ln ( 3 2 ) 17546 \boxed{1728a + 5184b = 41472\ln(\dfrac{3}{2}) - 17546}

54 a + 108 b = 43 \boxed{54a + 108b = -43}

a = 15482 41472 ln ( 3 2 ) 864 \implies a =\dfrac{15482 - 41472\ln(\dfrac{3}{2})}{864} and b = 20736 ln ( 3 2 ) 8085 864 f ( x ) = x 3 + 15482 41472 ln ( 3 2 ) 864 x 2 + 20736 ln ( 3 2 ) 8085 864 x b = \dfrac{20736\ln(\dfrac{3}{2}) - 8085}{864} \implies f(x) = x^3 + \dfrac{15482 - 41472\ln(\dfrac{3}{2})}{864}x^2 + \dfrac{20736\ln(\dfrac{3}{2}) - 8085}{864}x

Letting u = 1 + x d u = d x u = 1+ x \implies du = dx \implies

0 1 10 g ( x ) d x = 1 11 10 u 3 7 u 2 + 12 u 6 u 4 d u = 1 11 10 1 u 7 u 2 + 12 u 3 6 u 4 d u = \int_{0}^{\frac{1}{10}} g(x) dx = \int_{1}^{\frac{11}{10}} \dfrac{u^3 - 7u^2 + 12u - 6}{u^4} du = \int_{1}^{\frac{11}{10}} \dfrac{1}{u} - 7u^{-2} + 12u^{-3} - 6u^{-4} du = ( ln ( u ) + 7 u 6 u 2 + 2 u 3 ) 1 11 10 = (\ln(u) + \dfrac{7}{u} - \dfrac{6}{u^2} + \dfrac{2}{u^3})|_{1}^{\frac{11}{10}} =

ln ( 11 10 ) + 70 11 600 1 1 2 + 2000 1 1 3 3 = ln ( 11 10 ) 123 1331 0.00289846 \ln(\dfrac{11}{10}) + \dfrac{70}{11} - \dfrac{600}{11^2} + \dfrac{2000}{11^3} - 3 = \ln(\dfrac{11}{10}) - \dfrac{123}{1331} \approx \boxed{0.00289846}

and,

0 1 10 f ( x ) d x = 1 4 1 0 4 + 15482 41472 ln ( 3 2 ) 864 ( 1 3 1 0 3 ) + 20736 ln ( 3 2 ) 8085 864 ( 1 2 1 0 2 ) = \int_{0}^{\frac{1}{10}} f(x) dx = \dfrac{1}{4 * 10^4} + \dfrac{15482 - 41472\ln(\dfrac{3}{2})}{864}(\dfrac{1}{3 * 10^3}) + \dfrac{20736\ln(\dfrac{3}{2}) - 8085}{864}(\dfrac{1}{2 * 10^2}) =

2592 + 40 ( 15482 41472 ln ( 3 2 ) ) + 600 ( 20736 ln ( 3 2 ) 8085 ) 103680000 = \dfrac{2592 + 40 * (15482 - 41472\ln(\dfrac{3}{2})) + 600 * (20736\ln(\dfrac{3}{2}) - 8085)}{103680000} = 10782720 ln ( 3 2 ) 4229128 103680000 0.00137817 \dfrac{10782720\ln(\dfrac{3}{2}) - 4229128}{103680000} \approx \boxed{0.00137817}

0 1 10 g ( x ) f ( x ) d x 0.00152029 \implies \int_{0}^{\frac{1}{10}} g(x) - f(x) dx \approx \boxed{0.00152029}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...